PENGARUH DISIPLIN, MOTIVASI DAN SERTIFIKASI TERHADAP KEPUASAN DAN KINERJA GURU DI SMP KABUPATEN TAPIN - Jailani (JURNAL KINDAI, 2020)
Abstract:The aim of this study are analyzing (1) the influence of discipline to the satisfaction of teachers’ performance, (2) the influence of motivation to teacher’s performance satisfaction, (3) the significant influence of profession allowance to teachers’ satisfaction performance, (4) the influence of discipline to the teachers’ performance, (5) the influence of motivation to teachers’ performance, (6) the influence of profession allowance to teachers’ performance, and (7) the influence of work’s satisfaction to the junior high school teachers’ performance in Tapin regency. The population was all of the state junior high school teachers in Tapin regency which consisted of 275 teachers and the sample used was 163 teachers were taken by using slovin formula. The data analyzed using the software of SPSS 22. The activities of data analysis were using path analysis. The results of the study show that: (1) discipline has direct influence to the work’s satisfaction teachers’ performance (2) motivation has direct influence to the work’s satisfaction teachers (3) profession allowance has direct influence to the work’s satisfaction teachers in Tapin regency (4) discipline has direct influence to teachers’ performance (5) motivation has direct influence to teachers’ performance (6) profession allowance has direct influence to teachers’ performance in Tapin regency, and (7) work’s satisfaction has direct influence to the state junior high school teachers’ performance in Tapin regency. Keywords: Discipline, motivation, profession allowance, satisfaction and teachers’ performance Abstrak: Penelitian bertujuan untuk menganalisis(1) pengaruh disiplin terhadap kepuasan kerja guru, (2) pengaruh motivasi terhadap kepuasan kerja guru, (3) pengaruh sertifikasi terhadap kepuasan kerja guru, (4) pengaruh disiplin terhadap kinerja guru, (5) pengaruh motivasi terhadap kinerja guru ,(6) pengaruh sertifikasi terhadap kinerja guru SMP di Kabupaten Tapin, dan (7) pengaruh kepuasan kerja terhadap kinerja guru. Populasi dalam penelitian ini adalah semua guru SMP Negeri yang ada di Kabupaten Tapin yang berjumlah 275 orang. Sampel yang digunakan adalah 163 orang diambil dengan menggunakan rumus slovin. Analisis data menggunakan software SPSS 22. Hasil penelitian menunjukkan bahwa: (1) Disiplin berpengaruh langsung terhadap kepuasan kerja guru (2) motivasi berpengaruh langsung terhadap kepuasan kerja guru, (3) sertifikasi berpengaruh langsung terhadap kepuasan kerja guru, (4) disiplin berpengaruh langsung dantidak langsung terhadap kinerja kerja guru (5) motivasi berpengaruh langsung dan tidak langsung terhadap kinerja (6) sertifikasi berpengaruh langsung dan tidak langsung terhadap kinerja guru, dan (7) kepuasan kerja berpengaruh langsung terhadap kinerja guru SMP Negeri di Kabupaten Tapin Kata kunci: Disiplin, motivasi, sertifikasi, kepuasan dan kinerja guru